COMPENSATION MECHANISMS FOR DAMAGE CAUSED BY TERRORIST ACTS - Pilipović, Dejan (Politeia, 2023)
The issue of compensation for the damage caused by a terrorist act is relevant and important today, especially in the context of selection of mechanisms or models of compensation. For that reason, domestic and comparative positive legal solutions, case law, and legal literature are analyzed. This paper aims to show that there are several mechanisms of compensation that the legislator can choose and that they are not necessarily mutually exclusive, as well as that the current legal situation in the Republic of Srpska regarding this issue is not satisfactory and that one could consider improving the model provided by Yugoslav Law on Obligations (’ZOO’), which has been adopted by all of the former Yugoslav republics. For quality selection of mechanisms, it is necessary to confront attitudes about the need for a special case of liability for the damage due to a terrorist act, with attitudes about possible other compensation mechanisms outside the rules of tort law (for example,existence of certain funds for reparation, insurance, and alike). The paper uses the dogmatic and normative method, comparative law and sociological method, historical method, and the method of conceptual analysis.